Editorial Volume 9, Issue 2 - Monir Mir (Australasian Accounting, Business and Finance Journal, 2015)
There are five excellent studies which are published in this issue of Australasian Accounting, Banking and Finance Journal (AABFJ). As summarised below, out of these five studies, four of the studies have investigated and explored various accounting, finance and accountability issues of emerging and developing economies. Although more needs to be done, it is encouraging to observe that researchers from developing and emerging economies have been making progress in disseminating their research findings to the interested global communities.
Keywords: Editorial AABFJ June 2015